Water balance studies using a geographic information systems (GIS) approach. - Dizon, Cornelio Q. (Philippine Engineering Journal)
A surface water balance model for Ni Khu Hu and Tatha watersheds was developed by applying remote sensing and water balance modelling using a geographic information system. The study area is located at Thong Pha Phoom district, Kanchanburi province, western part of Thailand. The annual climatic data of the study area was used to determine the available water from the water balance equations. The LANDSAT TM image of the area was classified by image processing to produce the land use map. GIS modelling produced GIS maps of rainfall, evapotransportation, land use, soil, slope, excess moisture and surface runoff.